2020
DOI: 10.3390/ijerph17030915
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Incidence of Lung Cancer by Histological Type in Korean Adults: A Korean National Health Insurance Service Health Examinee Cohort Study

Abstract: Studies have reported associations between long-term exposure to ambient air pollution and lung cancer. However, there have been inconsistent reports of such associations with lung cancer by histological type. Thus, the aim of this study was to assess the association of long-term exposure to particulate matter with an aerodynamic diameter up to 10 μm (PM10) and nitrogen dioxide (NO2) with lung cancer incidence by histological subtype in South Korea. This population-based cohort study included 6,567,909 cancer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…There was also an adverse association of ambient PM 10 concentrations and total lung cancer incidence in the EAGLE study (Environment and Genetics in Lung Cancer Etiology), consisting of 2099 cases and 2120 controls in the Lombardy Region of Italy (odds ratio [OR] per 10 µg/m 3 , 1.28; 95% CI, 0.95‐1.72), with somewhat stronger findings for squamous cell carcinoma (OR per 10 µg/m 3 , 1.44; 95% CI, 0.90‐2.29) 77 . In a large‐scale South Korean study that included 6.5 million participants from a national health insurance database, there was no overall association of either PM 10 or NO 2 concentrations and incident lung cancer, but there was an adverse association of PM 10 and adenocarcinoma in male smokers (HR per >60.9 vs <50.40 μg/m 3 , 1.14; 95% CI, 1.03‐1.25) 78 . Further research on air pollution and lung cancer by histologic type is needed.…”
Section: Epidemiological Studies Of Outdoor Air Pollution and Lung Camentioning
confidence: 99%
“…There was also an adverse association of ambient PM 10 concentrations and total lung cancer incidence in the EAGLE study (Environment and Genetics in Lung Cancer Etiology), consisting of 2099 cases and 2120 controls in the Lombardy Region of Italy (odds ratio [OR] per 10 µg/m 3 , 1.28; 95% CI, 0.95‐1.72), with somewhat stronger findings for squamous cell carcinoma (OR per 10 µg/m 3 , 1.44; 95% CI, 0.90‐2.29) 77 . In a large‐scale South Korean study that included 6.5 million participants from a national health insurance database, there was no overall association of either PM 10 or NO 2 concentrations and incident lung cancer, but there was an adverse association of PM 10 and adenocarcinoma in male smokers (HR per >60.9 vs <50.40 μg/m 3 , 1.14; 95% CI, 1.03‐1.25) 78 . Further research on air pollution and lung cancer by histologic type is needed.…”
Section: Epidemiological Studies Of Outdoor Air Pollution and Lung Camentioning
confidence: 99%
“…Regarding the cancer types, several studies have shown a strong association between PM exposure and adenocarcinoma development (72,73). For each 10 µg/m 3 increase in ambient PM 2.5 , the risk of adenocarcinoma significantly increased (72).…”
Section: Influence On Lung Cancer Pathologic Typementioning
confidence: 99%
“…PM is divided according to its aerodynamic diameters into PM 10 (≤10 µm), PM 2.5 (≤2.5 µm), and ultrafine particles (UFPs) (≤0.1 µm). PM 10 contains all of the smaller fractions, and all of them are deposited in the respiratory tract during breathing [5][6][7][8][9]. PM 10 is made up of a variety of metals, such as zinc, copper, and vanadium; biological agents, such as pollen, bacteria, and endotoxins; and polycyclic aromatic hydrocarbons (PAH), including benzo(g)perylene (BghiP), dibenzo(a)anthracene (DBahA), and benzo(a)pyrene (BaP).…”
Section: Introductionmentioning
confidence: 99%